Colonial missionaries' papers from America and the West Indies, 1701-1870. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2009)
This collection offers a range of documents which reveal details of the lives the missionaries of the USPG really led. Starting with the formation of the USPG by Royal Charter in 1701, the reports, letters, minutes and accounts of places like Canada in the eighteenth to nineteenth century inform the reader about the colonists' attitudes and perceptions of American and other colonies during this period. Several documents in this collection feature commentary, directly or indirectly, on relations between the colonisers and the first nations such as the Iroquois and Algonquians including the Address of Indian sachems to Queen Anne. While missionaries first started working in the Gold Coast of Africa from 1752, work in Asia and India was first chronicled as a subject in itself nearly sixty years later in around 1815. The annual sermons of the society's preachers provide an opportunity to observe how various verses from the bible are used, to assert the value of the society's mission, during different phases within it.
Date range: 1701-1870.
Keywords: Missions -- America -- History; Missions -- West Indies -- History